Does gender diversity matter for green innovation?. (6th May 2019) - He, Xiaoping; Jiang, Shuo
Abstract: This study empirically investigated the relationship between board gender diversity and firm's green innovation, using panel data of public companies of China's manufacturing. Green product innovation was assessed by "green" patents and green process innovation assessed by environmental management certification. The endogeneity problem that resulted from self‐selection of gender diversity was addressed by means of extended probit regressions with an instrumental variable, and the instrumental variable was elaborately constructed based on changes in directorships. The findings show that occurrence of green innovation at the firm‐level is systematically related to female board representation. Specifically, women can exert a sizable and positive effect on green innovation, once they enjoy at least two seats on the boards; a further increase in representation of women on the boards can increase the likelihood of green product innovation rather than the likelihood of green process innovation. These results were robust to various regression specifications and alternative samples. The study provides empirical evidence that women at the top management can play a positive role in developing firm's active environmental strategies, and the conclusions are of practical implications for improving corporate governance along the environmental dimension.